Pengaruh Fluktuasi Harga Nener Bandeng Terhadap Etos Kerja Petani Pembudidaya di Kabupaten Buleleng, Bali - Thavia Aisyah Shinta Aprilla; Imam Hanafi; Apri I Supii (Faculty of Science and Technology University Ibrahimy, 2024)
Milkfish fry or nener is one of the leading commodities in Buleleng Regency, Bali. The fluctuating price of milkfish fry and the relatively large production and marketing margins cause a price difference between the selling and buying prices of milkfish fry, which can affect the work ethic of the farmers. This research uses a quantitative method with a simple linear regression approach to analyze the impact of fluctuations in the price of milkfish on the work ethic of cultivators. The purpose of the research is to further analyze the impact of fluctuations in the price of bandeng fish fry on the work ethic of fish farmers in Buleleng Regency, Bali. Based on the research results, it can be concluded that fluctuations in the price of bandeng fry have a significant impact on the work ethic of farmers in Gerokgak District, Buleleng Regency. Simple linear regression analysis shows that there is a strong positive relationship between price fluctuations and work ethic.